The role of structural factors in the formation of gas sensing properties of TiO2 – Fe2O3 nanocomposites - Babaryka, Natallia E.; Sviridov, Dmitriy V. (Journal of the Belarusian State University. Chemistry, 2017)
TiO2 – Fe2O3 composites with iron oxide content in the range of 1–50 mol. % were synthesized by sol-gel method. By means of X-ray diffraction analysis, scanning electron microscopy and IR spectroscopy the dependence of composite structure on the oxide molar ratio and annealing temperature was established. With the use of the synthesized oxide materials semiconductor gas sensors were fabricated. The possibility of low temperature detection of ethanol vapor with sensor at power consumption of 20 mW was shown. Correlation between the gas sensing activity of the composites towards ethanol vapor and structural characteristics of the composites was revealed. The highest output signal value has been attained for TiO2 – Fe2O3 composite with 50 mol. % content of iron oxide heated below 400 °C. This material consists of two oxide phases (anatase and g-Fe2O3 ) and possesses a developed surface.
Keywords: oxide composite; chemical gas sensor; titanium dioxide; iron(III) oxide